المطالبات في عقود الانشاءات (الفيديك) - عبد الصاحب, علي مطشر; علي, علي داود (Journal of Legal Sciences, 2017)
FIDIC contracts are regarded as clear reflection for economic, social, technical developments in building working, which have imposed international direction to unify laws as view to connection, expand international interests, exceeding activities of largest contracting companies out of borders of their countries, where we find that most of national laws were made to depend on FIDIC model contracts that were worded by International Federation of Engineers And Consultants, the last one was the contract of constructing of buildings, designed engineering businesses by the employers issued in 1999 that is known as New Red Book which edited distinguished from previous editions by depending on designing presented by the employer or consultative engineer to be provided that the contractor makes to construct working under those designs regardless from quality of businesses, it is suitable for working of electrical, mechanical or civil engineering, this model accredited by Iraq lastly included in standard documents of contracts of execute public labor were issued by department of execute governmental contracts in ministry of planning  .                                                               Issue of this FIDIC new contract had distinguished between concept of claims and concept of disputes, where both of them have decided rules, certain effects, so it is necessary that this research exposes to be distinct between them . And in the other hand we view that claims in construction contracting contracts have become inevitable matter, any construction working does not away from claims demanded by the contractor or employer with each other , though overwhelmingly of claims were to the contractor which presented to against employer or against employer and consultant engineer altogether, may be he presents it against the contractor in subcontract, therefore those claims were become of effects of contract of constructions ( FIDIC ) as regard for what it forms of vital role to stir strive between contractor & employer . So this research had stated classification of claims, their causes, such as organizing them with showing the role of advisor engineer to check, deciding , receive informs related to claims, then explain how to avoid them and followed procedures to solve those claims.